2021
DOI: 10.1556/038.55.2020.018
|View full text |Cite
|
Sign up to set email alerts
|

Structural Characteristics and Content of Polyphenolic Compounds in Healthy Organs and Galls Induced by Allodiplosis crassa Kieff. and Jörg (Cecydomyiidae, Diptera) on Geoffroea decorticans (Hook. and Arn.) Burkart (Leguminosae)

Abstract: Chañar (Geoffroea decorticans- Fabaceae) is a tree from South America that is normally infected with galls originated by insects. One of its parasites is Allodiplosis crassa (Cecidomyiidae, Diptera) which produces globular galls with sticky prolongations. Since this plant has medicinal uses in Argentina, its infestation could alter the quality of the plant drug. The surface of insect-induced galls usually contains defensive features such as trichomes, increased hardness and an increase in the content of polyph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
1
0
0
Order By: Relevance
“…HCA were higher in leaves, and were not affected by the phenological stage. These results correlate with those found in Geoffroea decorticans extracts, in which leaves showed higher levels of HCA derivatives when compared to stems [33]. Chapel [16], working with Calluna vulgaris (L.) Hull, reported that the higher amounts of polyphenolic compounds, including HCA, were found in stems and leaves at all phenological stages except during flowering, while no significant differences in PA content were observed among different organs and phenological stages.…”
Section: Discussionsupporting
confidence: 82%
“…HCA were higher in leaves, and were not affected by the phenological stage. These results correlate with those found in Geoffroea decorticans extracts, in which leaves showed higher levels of HCA derivatives when compared to stems [33]. Chapel [16], working with Calluna vulgaris (L.) Hull, reported that the higher amounts of polyphenolic compounds, including HCA, were found in stems and leaves at all phenological stages except during flowering, while no significant differences in PA content were observed among different organs and phenological stages.…”
Section: Discussionsupporting
confidence: 82%